(untitled) (The Peerian Journal, 2025)
Sustainable tourism has become an international method relied upon by international tourism organizations. It’s about maximizing positive impacts and minimizing negative impacts. Contrary to the general concept, it is not considered financially costly, as its implementation depends on three important aspects, the first of which is the financial return for tourism project owners, and the second is the social dimension, considering that these institutions are part of the local community and must benefit from local expertise and competencies as much as possible. The third dimension is the environment. These institutions are treated as part of the environment and therefore natural resources of water, energy, plants and natural life must be preserved to ward off any risks of degradation problems. This leads to integration into existing and future tourism facilities. The study focuses on answering the following question: What is the role of tourism in achieving sustainable development? The researcher used the social survey approach, choosing a proportional random sample, by distributing the study questionnaire to a sample of workers at the Ministry of Tourism, and the sample amounted to 55 workers.